Developing a UKM Activity Application for Universities in North Jakarta Using Scrum - Christianto, Kevin; Lee, Francka Sakti; Witari, Putu Sita; Andry, Johanes Fernandes; Budiyantara, Agus (Universitas Bina Darma, 2024)
Student Activity Units (UKM) plays an important role in supporting the development of student skills outside of academic activities. However, the management of UKM activities often faces obstacles in communication, administration, and membership management. This study aims to develop a UKM Activity Application designed to improve the operational efficiency of UKMs at Universities in North Jakarta. This application is equipped with key features such as member registration, activity management, attendance, and transparency of financial administration. The development was carried out using the Scrum method, which involves an iterative process starting from user needs analysis, product backlog preparation, to feature development in sprints. Daily stand-up meetings are held to monitor progress, and sprint reviews are used for evaluation and adjustment. The final result of this study is an application that is able to improve the efficiency of UKM activity management, strengthen communication between members, and increase student involvement in campus activities. This application is expected to be a modern digital solution to facilitate the management of UKMs in the university environment.